Analisa terhadap Penerapan Timeframe pada Perumahan Winner Flower House Punggur - Edrick Ottoh Wijaya; Petrus Haryanto Wibowo; Usmanul Hayadi Umar (Journal of Civil Engineering and Planning (JCEP), 2022)
This research will discuss about Winner Flower housing development The house which will later function as a residence, shop and apartment, and has facilities such as a club house and a swimming pool. This study aims to estimate the time for material procurement based on the time schedule for the construction project of the Punggur Flower House Winner. The method used to determine the estimated time is the conventional method, where the scheduling process is the scheduling process where the measurements are taken, in planning meetings, in measuring, and making scheduling times more regular and systematic. This research will discuss about Winner Flower housing development The house which will later function as a residence, shop and apartment, and has facilities such as a club house and a swimming pool. The estimated work plan for this project is 52 weeks and the realization of this project is 52 weeks. Thus it can be concluded that the processing time until the completion of the work is not delayed.